Kundskab og indvielse – En ikonografisk tolkning af udvalgte B-brakteater - Laursen, Kent O. (Kuml, 2006)
Knowledge and initiation An iconographic interpretation of selected B-bracteates Many theories concerning the identification of the motifs on the bracteates have been put forward through the years. A certain category of pictorial elements consisting of abstract and geometrical forms are often treated as unimportant with respect to the constitution of the content – as opposed to the figural elements, which have played the main part in the search for the identification of the motif – even though they are highly characteristic of the form of the bracteates. An authoritative statement of this view is found in Mackeprang 1952, where these abstract signs are dismissed as mostly ornamental in function and expressions of horror vacui. In this article, I will try to establish a more central role for these abstract signs in the interpretation process and to show that these elements do in fact make sense; that they are important to the content of the motif, and that their semantic meaning does not elude us completely. To demonstrate this, I take as my example four closely related bracteate motifs of the so called B-type, which depict bearded and apparently naked men with the arms posed in a dynamic gesture and with prominent extended thumbs as its figurative qualities, along with prominent abstract symbols in the periphery of the motif, foremost of which are circular shapes characteristically grouped in threes, as its abstract pictorial elements (Fig.2). These I term extra somatic elements, i.e. objects outside the body of the central figure. Runic inscriptions are also found on the discs. It is difficult to read a coherent meaning from the runic inscriptions, with the exception of one specimen: “I, Glistening Eye, consecrate the runes.” The other texts are more oblique, with distortions of common formulaic words of which ōþal, “land right by inheritance,” is most significant for the following interpretation. As an interpretive framework, I suggest the theory that these motifs can be regarded as based on the religious concept of the gaining of supernatural knowledge in an initiation scenario. This suggestion is afforded by comparison with written sources. An important step in the identification of the content has been made by Hilda Ellis Davidson (1989) when she identified the raised hand with the prominent thumb as a gesture signifying the gaining of supernatural knowledge. In a narrative context, this motif is connected to the acquisition of a wondrous food or elixir, which bestows supernatural insight on the subject. A short introduction to the concept of initiations is given, summarizing the research of Arnold van Gennep, Mircea Eliade and Victor Turner. The fact that the scenario of the initiation is tripartite (Fig.1) is stressed: The scenes move from a state in which the ignorant subject is separated from ordinary life to a second state where extraordinary things can happen and where the subjects encounters “The Sacred” or “Wholly Other” and is thereby transformed as he receives numinous knowledge, which leads to the third and final state, in which he has reached a spiritual and socially higher state of being. Symbolism revolving around death and rebirth is a characteristic of this transformation of the subject. The middle state, the liminal phase, is central to the concept, because the subject is seen here as caught between absolute extremes, “betwixt and between” in the words of Turner. Notable research on the subject concerning the old Scandinavian religion is also summarized. Jere Fleck has identified a “knowledge criterion” in the succession to the Germanic kingship, in which the acquisition of numinous knowledge by the pretender to the crown is essential to his success. The most comprehensive recent research on the subject is by Jens Peter Schjødt, who provides a working model of what to expect from the structure and symbolism of an initiation in a pre-Christian Scandinavian context. It appears that the interplay between This and The Other World is essential, in that the numinous knowledge is always envisioned as an object to be extracted from its guardian in The Other World (which is most often The Underworld), generally characterized as feminine in semantic content, whereas the subject is always male. I begin the interpretation by rejecting the view that the rather large circular objects on the torso are supposed to signify female breasts, and that this in combination with the beard makes the figure an androgynous being. A version of this theory goes on to identify the figure with a sorcerer similar to the shamans of Siberia, where “ritual perversion” was practised to enhance the powers of the shaman (Motz 1994). This opinion is connected to an interpretation of the seiðr and ergi complex (specific Norse concepts of sorcery and defamation respectively) as belonging to the shamanism complex, which is debatable. Another understanding can be reached if we allow the breasts to be simply nipples on an otherwise masculine naked body. Significant parallels are found between this motif and the description by the Arab diplomat Ibn Fadlan of rites in connection with the burial of a chief or royal person among the Rus (Scandinavians) on the shores of the Volga River in A.D. 922. He describes how the closest relative to the sovereign (his heir) ignites the pyre by walking backwards naked with his one arm raised in front of him and his other arm on his back. This rite has been interpreted as a rite of succession. The nakedness and the gesture are homologous to the bracteate motif in question. I suggest that this rite is not an invention of The Viking Age by comparison with a juridical rite, the Chrenecruda, from the Frankish Law of Lex Salica, written in the late reign of Clovis, i.e. around 500 A.D. and contemporary with the bracteates. This law describes how the offender who can not pay the wergild must gather dirt from the four corners of his house, take up a position on the threshold of the door with his back to his nearest relative, who is standing outside the house, and throw the dirt on him over his own shoulder, whereby the obligation of paying wergild falls on the relative. The two rites can be seen as inversions of each other, the one a rite upgrading the social position of the subject, the other a rite of degradation. At this point, the concept of ōþal enters the picture. Whereas the offender in the Chrenecruda loses his ōþal, the successor to the crown gains his. I suggest that the ōþal in the Rus case implies achievement of the “knowledge criterion”, which would make the function of the rite a transferral from The other World – i.e. the funeral pyre as a manifestation of the Kingdom of Death – of numinous knowledge to the new sovereign. As regards the motif on the bracteates, it can be demonstrated that numinous knowledge in the pre-Christian tradition is characteristically represented as a group of three objects. I further suggest that the reason for representing the groups of three extra somatic objects three times, in three different places, is connected to the conception that the numinous object must go through a cyclic journey through the cosmos in order to be refined and become fruitful. This is reflected in the myth of the acquisition of the mead of poetry, where wisdom in the embodied form of the god Kvasir is manufactured into mead contained in three vessels and placed in The other World, before being brought back to This World for use again by Odin. This conception is analogous to the structure of an initiation rite, and the cosmological implications are reflected in the microcosmic body, where oppositions such as front-back and head-abdomen are active structuring metaphors. In this way the gesture, nakedness and the different positions of the extra somatic objects on the motif (that is, their positions according to the different parts of the body of the central figure) reflect the progression of an initiation. It is not a coincidence that the comprehensible runic text speaks of the consecration of esoteric knowledge (runes) by a first person speaker (Glistening Eye), which can be seen as a speech act marking the critical point in a rite of initiation, namely the acquisition of numinous knowledge. By insisting on the importance of the extra somatic symbols in the motif and identifying them as objects of numinous knowledge, combined with the notion of the body as a classificatory system seen in the context of pre-Christian cosmology, a new understanding of this motif has been reached where the motif can be interpreted as a rite of initiation or succession of a sacral chief. This is an alternative to the common opinion that shamanism is the key concept to unlocking the motif. The common occurrence of the gesture with the thumb and the extra somatic symbols on the bracteates as a whole suggest that the perspective put forward here might possibly have a wider application. Kent O. Laursen The Institute of Anthropology, Archaeology, and Linguistics University of Aarhus Moesgaard